Generation and characterization of ScxCre transgenic mice. Issue 4 (13th March 2013) - Sugimoto, Yuki; Takimoto, Aki; Hiraki, Yuji; Shukunami, Chisa
<x xml:space="preserve">Abstract</x> Scleraxis (Scx) is a basic helix‐loop‐helix transcription factor that is a marker for the tendon/ligament cell lineage. The ∼11 kb genomic region from the mouse Scx gene locus faithfully recapitulates the endogenous Scx expression pattern in ScxGFP transgenic (Tg) mice. We have established two Tg mouse lines expressing Cre‐recombinase (Cre) using this regulatory region (ScxCre‐L and ScxCre‐H). The specificity and efficiency of Cre recombination in these Tg lines are evaluated by crossing with Rosa‐CAG‐LSL‐tdTomato (Ai14) or ROSA26R (R26R) reporter mice. The recombination in ScxCre‐H;Ai14 mice is efficiently achieved in the endogenous Scx expression domains including the branchial arches, the syndetome, and the lateral plate mesoderm. Further analysis of ScxCre‐H;Ai14;ScxGFP embryos reveal that expression of the ScxGFP transgene largely overlaps with Cre activity detected by tdTomato at embryonic day 12.5 (E12.5). In ScxCre-L;R26R or ScxCre-H;R26R neonates, Cre activity is detected in tendons, ligaments, intervertebral discs, joints, and cartilage around the chondro‐tendinous/ligamentous junction, the prospective enthesis. The present results suggest that ScxCre Tg lines are useful for targeting the gene specifically in the Scx‐expressing domains. genesis 51:275–283. © 2013 Wiley Periodicals, Inc.